A case for ecoscenography: Cultivating the continuous potential of things in performance design. Issue 1 (1st July 2018) - Beer, Tanja
The Ecological Turn offers a unique perspective on the cyclic and continuous potentiality of things in scenographic practice. This Is Not Rubbish is an ecoscenographic project that investigates the journey of a material rescued from landfill, and its capacity to create immersive performance spaces and wearable artefacts. Inspired by new materialist notions of inhuman agency, the project seeks to dissolve the boundaries between more-than-human actants, installation and costume, site and material. The visual essay examines the potential for ecoscenography to lead to new modes of practice in scenography, where expanded ideas of material entanglement, across bodies, ecosystems and built environments, are central to performance design.